138k views
3 votes
5 (u - 5) + 6u = 8 solve for u and simplifly your answer as much as possible

User Nick Bray
by
4.3k points

1 Answer

4 votes

Answer:

u = 3

Explanation:

Step 1: Distribute 5 in u - 5


\displaystyle{5\cdot u - 5\cdot 5 +6u=8}\\\\\displaystyle{5u-25+6u=8}

Step 2: Add like terms together (u-term)


\displaystyle{11u-25=8}

Step 3: Add both sides by 25


\displaystyle{11u-25+25=8+25}\\\\\displaystyle{11u=33}

Step 4: Divide both sides by 11


\displaystyle{(11u)/(11)=(33)/(11)}\\\\\displaystyle{u=3}

Answer Check

Step 1: Substitute u = 3 in the equation


\displaystyle{5(3-5)+6(3)=8}

Step 2: Evaluate & Simplify


\displaystyle{5(-2)+18=8}\\\\\displaystyle{-10+18=8}\\\\\displaystyle{8=8}

Since the equation is true after substituting u = 3. Therefore, the answer is u = 3.

Please let me know if you have any questions!

User Virgiliu
by
4.8k points